15 Deathbed etiquette-support for being at the bedside of the person you love. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Gadoud, Amy; Sanders, Karen; Nwosu, Amarachukwu; Elverson, Joanne; Bassett, Lynn; Doherty, Margaret
Abstract : Background: People in the UK are often uncomfortable with supporting the dying. As the population ages we are less likely to have supported a loved one who has died. Methods: The Centre for the Art of Dying Well, with palliative care experts and experts by experience, created a resource to support someone at the deathbed of a loved one. This was updated for the COVID-19 pandemic. This abstract describes the wider public engagement with this resource, using content analysis to evaluate public sentiment and understanding of it. Results: Release of the original Guide coincided with a report assessing preparedness for supporting someone who is dying, a podcast and a press release. It was widely quoted in the news media with reports in The Times; local and national news (Radio Oxfordshire, Talk Radio, Channel 5 News). Google Analytics demonstrated 7, 341 unique visitors to the Guide spending, on average, 2 minutes 2 seconds reading it. The version updated for COVID-19 was widely cited in the Financial Times, the Daily Mail, the Sun and Vatican News and an interview on 5 Live Radio. Based on an analysis of article comments, public sentiment and understanding were shown to be varied including very positive and very negative reactions. There was widespread individual engagement online and offline and also endorsement by organisations such as Marie Curie and Health Improvement Scotland. The Guide for COVID-19 had 2, 545 unique page reviews with users spending on average 2 minutes 50 seconds on the page. Analysis of Twitter data demonstrated a wide level of engagement with the content of both guides, and discussions occurring across a diverse range of individuals. Conclusions: There has been widespread uptake. Public reception, as evaluated in the content analysis, will guide future research to explore the Guide's impact.